EKSISTENSI PENGALIHAN PENANGGUNGJAWABAN MENCARI NAFKAH TERHADAP ISTRI MENURUT PERSPEKTIF ILMU FIKIH DAN ILMU PSIKOLOGI - Syaifi Udzkhiyatin Nisa; Sabilul Muhtadin (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2023)
Marriage is a way to form a family with sacred ties and based on religious teachings. The existence of this marriage bond will give rise to rights and obligations. Among the duties of a wife are to obey her husband and maintain his honor. Meanwhile, the husband's obligations include the obligation to provide maintenance. Brebes is the second largest district in Central Java Province. This research aims to determine and analyze the impact of the transfer of earning a living on the wife, the factors causing it and the law on the transfer of earning a living from the perspective of Islamic jurisprudence and psychology. This research uses a qualitative approach with a case study type. The results of this research show that: (1) there are 4 negative impacts and 2 positive impacts experienced by the transfer of responsibility for earning a living to wives in Brebes District, (2) there are 4 factors that cause wives to choose to earn a living in Brebes District, ( 3) The transfer of responsibility for earning a living to the wife gives rise to laws in jurisprudence based on several circumstances and also the existence of a wife who plays a dual role can affect marital and family harmony, as well as affect the wife's mental condition.